The Effect Of Perceived Value And Price On Repurchase Intention With Brand Trust As A Mediating Variable From An Islamic Business Perspective - fadil, ahmad; Zuliansyah, Ahmad; Utamie, Zathu Restie (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The fast-food industry in Indonesia has exhibited substantial growth, driven by increasingly dynamic lifestyles and the demand for expedient, practical, and cost-effective meals. Amid escalating market competition, business stakeholders are compelled to generate added value and employ effective marketing strategies to sustain consumer loyalty. This study aims to analyze the influence of perceived value and price on repurchase intention among consumers of Mie Gacoan, a fast-food establishment in Bandar Lampung, with brand trust serving as a mediating variable. This research adopts a quantitative methodology grounded in the Theory of Planned Behavior, which posits that consumer behavior is shaped by perceptions, attitudes, and trust in a brand. Data were collected via questionnaires administered to a sample of 100 respondents and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The findings demonstrate that perceived value has a significant positive impact on repurchase intention but a negative impact on brand trust. Conversely, price has a significant negative impact on repurchase intention, with no significant effect on brand trust. Additionally, brand trust exhibits a strong influence on repurchase intention and mediates the relationship between perceived value and repurchase intention; however, it does not mediate the relationship between price and repurchase intention. These insights underscore the importance of building brand trust as a pivotal factor in fostering consumer loyalty, alongside the consideration of perceived value and pricing strategies in marketing policy formulation. The model's Goodness of Fit (GoF) value of 0.464 indicates a robust model performance in explaining the variable of repurchase intention.